ANALISIS KRITIS TANTANGAN PENDIDIKAN ISLAM DALAM MENGHADAPI ERA DISRUPTION 4.0 - Mita Suryanti; Agus Sujarwo; An An Andari (UNISAN JURNAL, 2024)
The rapid development of technology is a sign of an era of disruption. Human resources are very important in terms of education. The human resources of educational institutions consist of educators and teaching staff. The role of teachers is very important in education, including Islamic education. It is hoped that Islamic education can take advantage of the various opportunities that exist in this shifting era. Nonetheless, educators face challenges as well as opportunities. This research uses qualitative descriptive analysis to critically analyze the problems of Islamic educators in the era of disruption 4.0. Research shows that the difficulties faced by Islamic educators in the Disruption 4.0 era encourage a shift in the educational paradigm and require teachers to teach creativity, critical thinking and collaboration. Islamic education must maintain religious and moral values while taking advantage of digitalization opportunities to adapt to technological advances. Islamic education will make a significant contribution to creating a superior and competitive generation through the development of relevant skills and the use of technology